2010
DOI: 10.1016/j.jtcvs.2009.09.034
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Custodiol-N, a novel organ preservation solution, on ischemia/reperfusion injury

Abstract: Custodiol-N improves myocardial and endothelial function during the critical phase of reperfusion after heart transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
28
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 22 publications
2
28
0
Order By: Relevance
“…LK 614 also showed strong protection in the current study. The new preservation solution, as base solution (N46) and supplemented by iron chelators (Custodiol-N), showed largely improved liver and heart preservation in different experimental studies [20,23,24], and will, based on the encouraging results described here, soon be tested in an experimental model of lung transplantation.…”
Section: Discussionmentioning
confidence: 81%
“…LK 614 also showed strong protection in the current study. The new preservation solution, as base solution (N46) and supplemented by iron chelators (Custodiol-N), showed largely improved liver and heart preservation in different experimental studies [20,23,24], and will, based on the encouraging results described here, soon be tested in an experimental model of lung transplantation.…”
Section: Discussionmentioning
confidence: 81%
“…As shown in earlier studies, a fundamental pathway for cardiac damage during reperfusion includes marked increases in the amount of superoxide anion, hydrogen peroxide, and possibly singlet oxygen production [20]. In line with these findings, it has been demonstrated that a Bretschneider’s solution, developed as a cardioplegic solution in routine cardiac surgery, could effectively reduce energy requirements and prevent damages during reperfusion, due its role as a strong reducing agent of hydroxyl radicals and reactive oxygen species (ROS), leading to improved myocardial protection via controlling cellular oxidative stress levels [21, 22]. Therefore, preventing or at least to controlling increases in the oxidative stress levels of donor hearts during cold storage seems to be a crucial part of heart transplantation in cardiac surgery.…”
Section: Discussionmentioning
confidence: 95%
“…It is worth nothing that normal preoperative PVR does not rule out increased PVR and acute RV failure after HTx. Organ preservation and cardiopulmonary bypass also have deleterious effects on ventricular function [22][23][24] . The previous common practice of using oversized donors for recipients with PH has been found unnecessary 25 .…”
Section: Discussionmentioning
confidence: 99%